Building occupant’s perspective on the maintenance management at the apartment in Putrajaya / Nik Nur Aishah Nor Affendi and Nor Amin Mohd Radzuan - Nor Affendi, Nik Nur Aishah; Mohd Radzuan, Nor Amin (2023)
Heritage buildings play a crucial role in preserving a nation's cultural identity and history. In Malaysia, these buildings hold significant importance, reflecting the country's diverse heritage and serving as tangible reminders of the past. The issue is due to costing, ongoing maintenance after renovation, conservation plan, conserver duty and labour shortage and choice in material. This research focuses on the challenges of maintenance in Seri Menanti. This research implements a qualitative methodology that needs to interview the personnel of Lembaga Muzium Negeri Sembilan. The significant of the challenges is cost due to limited resources available and renovation. Besides, The materials are also difficult to find with the original. The outcome of the research enhances acquiring additional information on the subject and in guiding the public to a deeper understanding of the challenges involved. The long-term planning and decision-making help in further practices to ensure that the heritage building can be preserve for future generation.